Calitatea vieții în România: 1990-1996 - Precupețu, Iuliana; Preoteasa, Ana Maria; Pop, Cosmina (Calitatea Vieții, 2007)
The present paper describes the dynamics of Romanians’ quality of life by using longitudinal data, covering the period 1990–2006. The five dimensions of quality of life are: the living conditions, the social environment, the political sphere, the work life and the personal life. Research data describe the levels registered by indicators during time and allow characterising the life realms in their dynamics. This study contains primary research data which could be interesting to those interested in quality of life and related domains (social policy, economic policy, etc). It comprises evaluations of objective conditions as well as people’s satisfactions regarding those states. Results show that, overall, we can speak of a relatively low level of quality of life, with a positive trend of most indicators, starting in 2003 and continuing in 2006.